Impact of the COVID-19 Pandemic on Different Groups of SMEs in Germany and Their Recovery - Volker Zimmermann; Fritzi Köhler-Geib (Intereconomics, 2023)
Using Germany as an example, this article examines how different groups of small andmedium-sized enterprises were impacted by and recovered from the COVID-19 pandemic.The study found that at the onset of the pandemic, turnover losses were experienced notjust by enterprises regarded as poor performers, i.e. small businesses or those with lowcredit ratings, but also, and in particular, by high-performing companies. However, the latterrecovered faster from the impact of the pandemic than other businesses. This suggeststhat this group developed the capacity to successfully respond to changes in the businessenvironment and seize possible opportunities even before the pandemic hit. Such enterprisesshow themselves to be particularly crisis-proof. Thanks to the wide range of enterprises'adaptation measures and state support measures, the financial capacity of small andmedium-sized enterprises in Germany was hardly diminished by the pandemic.
Keywords: M21; O16; 330; SMEs; Coronavirus; Germany; KMU; Coronavirus; Deutschland